2020
DOI: 10.1007/s00213-020-05591-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of suppressing the biological stress systems on social threat-assessment following acute stress

Abstract: Rationale Stress is associated with increased sensitivity to threat. Previous investigations examining how stress affects threat processing have largely focused on biomarker responses associated with either the sympathetic-nervous-system (SNS) or the hypothalamus-pituitary-adrenal (HPA) axis. Objectives We pharmacologically suppressed activations of SNS, HPA, or both, prior to stress and investigated how each stress system modulates social threat assessment. Methods One hundred sixty-one healthy men and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The observed inverse relationship between the HPA axis activity and negative affect possibly indicates a disruption of this feedback loop by morphine administration and is in line with a mood-buffering effect of cortisol (Het et al, 2012;Het & Wolf, 2007). Accordingly, it was recently shown that pharmacological HPA axis suppression, by means of dexamethasone administration, blunts the cortisol response to stress and increases negative mood, especially in women (Ali et al, 2017(Ali et al, , 2020.…”
Section: μ-Opioid Agonist Morphine Dampens Cortisol and Increases Negative Affect In Response To Stressmentioning
confidence: 73%
See 1 more Smart Citation
“…The observed inverse relationship between the HPA axis activity and negative affect possibly indicates a disruption of this feedback loop by morphine administration and is in line with a mood-buffering effect of cortisol (Het et al, 2012;Het & Wolf, 2007). Accordingly, it was recently shown that pharmacological HPA axis suppression, by means of dexamethasone administration, blunts the cortisol response to stress and increases negative mood, especially in women (Ali et al, 2017(Ali et al, , 2020.…”
Section: μ-Opioid Agonist Morphine Dampens Cortisol and Increases Negative Affect In Response To Stressmentioning
confidence: 73%
“…Accordingly, it was recently shown that pharmacological HPA axis suppression, by means of dexamethasone administration, blunts the cortisol response to stress and increases negative mood, especially in women [52,53].…”
Section: Morphine-blunted Cortisol Stress Response Is Associated With Increased Negative Affectmentioning
confidence: 99%
“…Of note, we did not find an association between TSST-induced changes in subjective stress and empathic accuracy (nor did we find an association between sAA and empathic accuracy). As outlined before, the human stress response involves multiple signals (e.g., changes in cortisol, sAA, and subjective stress, as measured here, as well as changes in heart rate variability and even neural activity) that each interact in complex ways to produce functionally nuanced outputs (Ali, Cooperman, et al, 2020; Hermans et al, 2011; Kukolja et al, 2008). Moreover, these signals are often dissociated (e.g., cortisol and subjective distress are often unrelated and may even function to compensate for one another; Ali et al, 2017; Ali, Nitschke, et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…They were asked four times: at the beginning of the task after the 3 minute-resting period (Time 0), then after each block of arithmetic task (Time 1 and 2) and another time at the very end after the 3 minute-recovery period (Time 3). A visual analogue scale is a fast and efficient way to assess the subjective stress level ( Ali et al., 2020 ; Fujiwara & Okamura, 2018 ; J. J. Liu et al., 2020 ; Nakamura et al., 2020) .…”
Section: Methodsmentioning
confidence: 99%